PEMINDAHAN TAPING FASA UNTUK PENYEIMBANGAN BEBAN PADA JARINGAN 3 FASA DENGAN MENDETEKSI ARUS NETRAL BERBASIS ARDUINO MEGA 2560 - Wicaksana, Pandu; Manan, Saiful (Gema Teknologi, 2017)
Pandu Wicaksana, Saiful Manan, in this paper explain that the load balance on the 3 phase 4 wire distribution system is very important. Continuous load imbalances can cause a decrease in the reliability of the electric power system and the quality of electrical energy. One consequence of an unbalanced load is the presence of a current flowing in a neutral introduction. The purpose of this study is to find out and analyze the current in a neutral conductor when the load conditions are unbalanced and when balanced. Load balancing is done by manual-remote, which means that the transfer of taping at a load is done by pressing the button that has been integrated with the HMI display. This software is also responsible for displaying current output from the sensor. That way, it can be seen that the current value of the neutral conductor before and after load balancing is done. That the current value of the neutral conductor will be smaller when the load is balanced compared to when the load between phases is not balanced.